"Imágenes de Galicia", Luís Seoane’s Printmaking in Buenos Aires - Dolinko, Silvia (Madrygal. Revista de Estudios Gallegos, 2017)
Over decades, Luís Seoane developed a multifaceted body of work with a special interest and prolific work in multiple art. With its inherent possibility of wide circulation, this production constituted one of the most significant aspects of his corpus. Thus, books were a privileged support for the wide dissemination of his images –especially woodcuts– depicting folk or legendary characters represented through a modern visual discourse. This article analyses Seoane’s printmaking work in Buenos Aires, focusing on the book Imágenes de Galicia (Images of Galicia), published by Albino Fernandez in 1978. Our main hypothesis is that the set of 72 woodcuts included in that publication condensed the imagery developed by the artist throughout his career. Seaone’s will to give graphic expression to folk stories and characters was one of his main strategies for public intervention, as it was a manifestation of his ethical commitment to Argentinean and Galician culture of the twentieth century.